2016 busy year for Global Movement of Moderates - New Sunday, Times (New Straits Times, 2017)
KUALA LUMPUR: 2016 has proven to be a successful year for the Global Movement of Moderates Foundation (GMMF) in a world of escalating tensions and against the backdrop of extremism.